Parables for the virtual movement, affect, sensation - Massumi, Brian (Durham Duke University Press, 2022)
Although the body has been the focus of much contemporary cultural theory, the models that are typically applied neglect the most salient characteristics of embodied existence-movement, affect, and sensation-in favor of concepts derived from linguistic theory. In Parables for the Virtual Brian Massumi views the body and media such as television, film, and the Internet, as cultural formations that operate on multiple registers of sensation beyond the reach of the reading techniques founded on the standard rhetorical and semiotic models. Renewing and assessing William James's radical empiricism and Henri Bergson's philosophy of perception through the filter of the post-war French philosophy of Deleuze, Guattari, and Foucault, Massumi links a cultural logic of variation to questions of movement, affect, and sensation. The new preface to the anniversary edition situates the book in relation to developments since its first publication, and summarizes its main concepts and how they have evolved"--
The autonomy of affect -- The bleed: where body meets image -- The political economy of belonging and the logic of relation -- The evolutionary alchemy of reason: Stelarc -- On the superiority of the analog -- Chaos in the ''total field'' of vision -- The brightness confound -- Strange horizon: buildings, biograms, and the body topologic -- Too-blue: color-patch for an expanded empiricism.
Includes bibliographical references (pages 333-342) and index.
Keywords: Affect (Psychology); Movement (Philosophy); Senses and sensation